Daya Antibakteri Ekstrak Etanol Ketepeng Cina (Senna alata) terhadap Staphylococcus aureus dan Escherichia coli secara In Vitro - Yacob, Taswin; Endriani, Rita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2010)
The benefit and efficacy of ketepeng cina (Senna alata) in the treatment of infection has shown that have antibacterialactivity, inhibiting and killing bacteria that cause infection. The objective of this study was evaluate the antibacterialactivity of ketepeng cina against Staphylococcus aureus dan Escherichia coli in vitro. This study was a laboratoryexperimental research which use completely randomized design with diffusion method. Ethanol extract of Sennaalata leaves devided into 4 doses, i.c. 100, 50, 25 and 12.5. Amoxiclave were used as positive control and aquadestnegative control. The data were analyzed by Analysis of Varian continued with Duncan’s Multiple Range Test. Theresult of this study showed that antimicrobial activity of ethanol extract Senna alata leaves inhibited the growth ofStaphylococcus aureus, but not Escherichia coli. The optimum effect was showed given by the concentration 100at 17.7 mm.